Lucas, Peter J. 2024. Printing Anglo-Saxon from Parker to Hickes and Wanley. With a Catalogue of Early Printed Books Containing Anglo-Saxon 1566–1705. Library of the Written World 105. Leiden: Brill. Pp. xxiv + 708. ISBN 9789004516977. - Kees Dekker (SELIM, 2025)
Book review of Lucas, Peter J. 2024. Printing Anglo-Saxon from Parker to Hickes and Wanley. With a Catalogue of Early Printed Books Containing Anglo-Saxon 1566–1705. Library of the Written World 105. Leiden: Brill. Pp. xxiv + 708. ISBN 9789004516977.